Visual journalism in the iberian press - Brigas, Joaquim; Gonçalves, Fátima; Gonçalves, Jorge (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
As a way of managing the growing volume and complexity of information that circulates today, graphic representations are increasingly used to add meaning to the information presented in the media, through efficient communication design. The visual culture itself, driven by technological evolution, has been redefining the forms of communication, which is why contemporary visual communication represents a great impact on society. This article presents the results and the comparative analysis of four Iberian press publications, focusing on the formal aspects of the newspapers and the space they dedicate to the different communicative elements. For this, two Portuguese and two Spanish newspapers were selected. The results indicated that the newspapers show a similarity in the use of graphic solutions, which corroborates a visual trend in communication design. The results also reveal that Spanish newspapers are more careful with graphic consistency.